Valorisation of waste glass in eco-friendly clay brick: influence on physico-mechanical properties and water absorption - Chew, Kai Ying; Majnis, Mohd Fadhil; Taib, Mustaffa Ali Azhar; Abu Bakar, Ayu Haslija; Jamail, Maliza Ismail (Universiti Teknologi MARA Shah Alam, 2025)
Clay bricks are widely used as building material all around the world. Natural clay is experiencing a constant reduction due to its continual use in the manufacturing of clay bricks. The depletion of clay resources has become a global issue, prompting many countries to limit the use of natural clay. This research study investigates the effect of waste glass addition on the physical-mechanical and water absorption properties of eco-friendly clay bricks, incorporating 0, 5, 10, 15, and 20 wt% of waste glass into the clay. The temperature of 900°C was used for the firing process of clay bricks. Compressive strength, linear shrinkage, bulk density, apparent porosity and water absorption of the eco-friendly clay bricks were tested. Incorporating 20 wt% waste glass into clay bricks improved mechanical and physical properties: compressive strength (+29.4%), bulk density (+11.3%), apparent porosity (−16.0%), and water absorption (−24.6%). The digital micrographs demonstrated a reduction in the porosity with the addition of waste glass. This study revealed that the addition of waste glass induced the formation of a glass-phase fused bond with the body of clay when subjected to high temperature. Waste glass can be added to clay brick as a partial substitute for natural clay, improving the physical-mechanical and water absorption properties of clay bricks.